The Legal Dimensions for Franchise Agreement - Sawalha, Khaled Mohammed Faleh; Hlail, Mounir Ali (Journal of Economic, Administrative and Legal Sciences, 2019)
This study aims to demonstrate the concept of commercial excellence, which is one of the distinct ways to open new investment opportunities and that the franchise contract represents a contractual relationship between the licensee and the licensee, in which the latter operates under the name, brand or trade reputation owned and associated with the first, Is separate from the licensed project. In this contractual relationship it is stipulated that technical assistance should be provided by the licensee to the licensee, but the licensee exercises some kind of control over the licensee’s business, in order to guarantee the quality of the products or services provided to consumers We have demonstrated the need to work on the development of contract formulas in the commercial franchise, and to find a detailed system for its practice and in a manner that protects this right through coordination between the concerned parties to organize the Franchise system, as well as work on creating the organizational climate to spread the culture and franchise industry to all activities. In the period prior to the contract, provided that such information is determined, with the limits of technical support, marketing, mandatory training and confidentiality.